Development of life cycle inventory and greenhouse gas emissions from damaged paddy grain as fermentation feedstock: a case study in Malaysia - Abu Bakar, Nurul Ain; Roslan, Ahmad Muhaimin; Hassan, Mohd Ali; Abdul Rahman, Mohammad Hariz; Ibrahim, Khairul Nadiah; Abdul Rahman, Muhammad Daaniyall; Mohamad, Rozyanti (Elsevier, 2022)
Glucose is an intermediate substance of various bio-based products in a biorefinery concept. A sustainable processing of biomass into glucose could provide alternative for managing waste of the paddy industry. A detailed model of glucose production life cycle inventory from the waste of the paddy industry, and evaluation of potential greenhouse gas was conducted from a cradle-to-gate approach in Malaysia. The foreground data for cultivation and milling of EPFG was based on real production data, while glucose production was based on laboratory study. The inventory highlighted the areas where the processing system would have the largest impact on raw materials, energy consumption, and emissions. This life cycle GHG quantifies the main hotspot for glucose production from paddy waste with agriculture at 74.6% and purification process at 5.3%, thus indicating a significant impact on the systems. The overall GHG impact of glucose production in mass allocation procedure produces 1.2 t CO2eq/t glucose. Finally, based on the comparison analysis results, converting paddy processing waste into glucose may be considered as an alternative for managing waste from paddy supply chain as the total emissions are within the second-generation feedstock biorefinery.